1996
DOI: 10.1097/00001648-199603000-00003
|View full text |Cite|
|
Sign up to set email alerts
|

Bladder Cancer Mortality Associated with Arsenic in Drinking Water in Argentina

Abstract: Inorganic arsenic (In-As) is known to be a human carcinogen, causing lung cancer by inhalation and skin cancer by ingestion. Ecologic studies in Taiwan have found a dose-response relation between ingestion of In-As from drinking water and bladder cancer, but questions have been raised concerning the validity and generalizability of the findings. Several areas of Argentina have had high exposures to arsenic from naturally contaminated drinking water, particularly the eastern region of the province of Córdoba. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
169
1
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(186 citation statements)
references
References 0 publications
13
169
1
3
Order By: Relevance
“…Some studies found that tap water with chlorine-and hence containing chlorination byproducts-may increase the risk of bladder cancer (Wilkins & Comstock, 1981;Gottlieb & Carr, 1982;Zierlier et al, 1986Zierlier et al, , 1988Cantor et al, 1987Cantor et al, , 1998McGeehin et al, 1993;Koivusalo et al, 1994;King & Marrett, 1996;Kiemeney & Schoenberg, 1996;Freedman et al, 1997). Arsenic in drinking water has also been associated with increased risk of bladder cancer (Chen et al, 1986(Chen et al, , 1992Wu et al, 1989;Bates et al, 1995;Hopenhayn-Rich et al, 1996;Chiou et al 2001), but it is unclear whether the levels of arsenic in drinking water from developed countries have any meaningful effect. It is also uncertain whether the apparent association reflects inadequate allowance for social class correlates of bladder cancer, since bladder cancer risk is elevated in smokers and in workers exposed to occupational carcinogens-and hence in lower social class individuals (La Vecchia et al, 1989, 1990Silverman et al, 1996;Negri & La Vecchia, 2001).…”
Section: European Journal Of Clinical Nutritionmentioning
confidence: 99%
“…Some studies found that tap water with chlorine-and hence containing chlorination byproducts-may increase the risk of bladder cancer (Wilkins & Comstock, 1981;Gottlieb & Carr, 1982;Zierlier et al, 1986Zierlier et al, , 1988Cantor et al, 1987Cantor et al, , 1998McGeehin et al, 1993;Koivusalo et al, 1994;King & Marrett, 1996;Kiemeney & Schoenberg, 1996;Freedman et al, 1997). Arsenic in drinking water has also been associated with increased risk of bladder cancer (Chen et al, 1986(Chen et al, , 1992Wu et al, 1989;Bates et al, 1995;Hopenhayn-Rich et al, 1996;Chiou et al 2001), but it is unclear whether the levels of arsenic in drinking water from developed countries have any meaningful effect. It is also uncertain whether the apparent association reflects inadequate allowance for social class correlates of bladder cancer, since bladder cancer risk is elevated in smokers and in workers exposed to occupational carcinogens-and hence in lower social class individuals (La Vecchia et al, 1989, 1990Silverman et al, 1996;Negri & La Vecchia, 2001).…”
Section: European Journal Of Clinical Nutritionmentioning
confidence: 99%
“…iAs is classified as a human carcinogen (IARC, 1987). Numerous epidemiologic studies have associated chronic exposure to iAs with increased prevalence of cancers of the skin, bladder, liver, lung, and stomach (Bates et al, 1995;Bates et al, 1992;Chen et al, 1992;Chen et al, 1985;Chiang et al, 1988;Chiou et al, 1995;Guo et al, 1997;Hopenhayn-Rich et al, 1996;Hopenhayn-Rich et al, 1998;Lewis et al, 1999;Smith et al, 1998;Smith et al, 1992;Tseng et al, 1968;Tsuda et al, 1995;Wu et al, 1989). Previous research of the effects of chronic exposure to iAs has focused primarily on its carcinogenic potential.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of groundwater with high As content causes poisoning-arsenotosis, leading to chronic and even lethal health effects (Borzonyi et al, 1992;Hopenhayn-Rich et al, 1996;Kurttio et al, 1999).…”
Section: Arsenicmentioning
confidence: 99%